Key ideas in the rule of law and the separation of powers - Beatson, Jack, 1948- (London, England : Zed Books, 2021)
"Prompted by the events following the 2016 referendum on EU membership and written by one of the leading public lawyers of our day, this book considers the rule of law and separation of powers by examining the relations between the different branches, and the mechanisms of accountability within our democracy. Since the referendum, attention has refocused on the relationship and respective powers and competences of the three branches of the state: the legislature, the executive and the judiciary. They have also placed strains on our unwritten constitution that have been unknown in modern times. The role of the courts and of the rule of law has been dramatically illustrated by recent litigation, most notably the decisions on whether legislation was needed to serve notice of the UK's intention to leave the EU and whether the prorogation of the Westminster Parliament in 2019 was a matter for the courts as opposed to a political question for government. It has also been highlighted by the debate about the rules and guidelines presented as rules made to deal with COVID-19. Set against this backdrop, the book answers the following questions: - How accessible is the law and how does it avoid arbitrariness? - How is access to justice protected? - How does our constitution reflect the separation of powers and the balance of responsibilities between law and politics? - How does our democracy enable majorities and protect minorities?"--
Overview -- Formal and substantive conceptions of the rule of law -- Dicey's rule of law and the twentieth-century critiques -- Accessibility of law -- Avoiding arbitrariness -- Access to justice -- An independent and impartial judiciary -- The separation of powers and the balance of responsibilities -- Enabling majorities and protecting minorities in our democracy.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Rule of law; Separation of powers; Constitutional & administrative law; Electronic books